Contribution of cultural interests to subjective well-being of youth in Serbia - Jokić, Biljana R.; Mrdja, Slobodan (Sociološki pregled, 2023)
Research shows that cultural interests contribute to subjective well-being, but results are not highly consistent. This study on the youth in Serbia (N = 453) is aimed at exploring: 1. factorial structure of favourite leisure activities, 2. their contribution to well-being, along with socio-demographics, physical health, and engagement on social networks, and 3. whether and how results differ depending on operationalization of the criterion variable (subjective happiness, SH vs. satisfaction with life, SWL). The results show that physical health and favourite leisure activities (cultural interests and folk & family) are significant predictors of both SH (along with sport and a larger number of social networks profiles) and SWL (along with expenditure for culture and home/entertainment).
Keywords: cultural participation; consumption; happiness; well-being; leisure